2015
DOI: 10.1177/2058460115602729
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of SPECT/CT in the diagnosis of occult scaphoid fracture

Abstract: Background *Equal contributors.Planar bone scintigraphy (PBS) is often advocated for diagnosing occult scaphoid fractures. PBS is a sensitive diagnostic modality, but lacks specificity, which may result in over-diagnosis.PurposeTo examine, in a pilot study, the potential additional value of single photon emission computed tomography (SPECT) combined with low dose computed tomography (CT) for the diagnosis of an occult scaphoid fracture.Material and MethodsTen patients that underwent combined PBS and SPECT/CT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…1% of all fractures) and often difficult to diagnose with conventional imaging. De Zwart et al compared SPECT/CT to planar bone scintigraphy in ten patients with carpal trauma and found more accurate anatomic description of fractures with SPECT/CT in three patients (de Zwart et al, 2015). Allainmat et al confirmed the superiority of SPECT/CT in the detection of posttraumatic bone lesions after carpal injury (Allainmat et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1% of all fractures) and often difficult to diagnose with conventional imaging. De Zwart et al compared SPECT/CT to planar bone scintigraphy in ten patients with carpal trauma and found more accurate anatomic description of fractures with SPECT/CT in three patients (de Zwart et al, 2015). Allainmat et al confirmed the superiority of SPECT/CT in the detection of posttraumatic bone lesions after carpal injury (Allainmat et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they demonstrated that the use of SPECT/CT-correlated images provided a definite diagnosis in 92% of skeleton lesions otherwise classified as indeterminate on using only SPECT. In a recent article, de Zwart et al 49 showed SPECT/CT to have a potential of being more accurate than planar scintigraphy imaging, as it uses anatomical information of the CT to discriminate among the scaphoid, other carpal bones and bone bruises. They concluded that SPECT/CT is superior to planar bone scintigraphy in the detection of occult fractures and presents additional information about the injury site and localization of the fracture, and the method could potentially serve as a future reference standard for studies concerning scaphoid fractures.…”
Section: Clinical Applications Using Single-photon Emission Ct/ctmentioning
confidence: 99%